PENGARUH SOSIALISASI MEDIA ORANG TUA DAN DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP KOMPETENSI SOSIAL ANAK - Berlianti, Diana; Krisnatuti, Diah; Djamaludin, M.D. (Jurnal Ilmu Keluarga dan Konsumen, 2015)
The low social competence of children can be caused by the many media containing antisocial behavior that is accessible by children and also the negative influence of peers. This study aimed to analyze the influence ofmedia socialization of parents and social support of peer group on the social competence of school-aged children. The study used a survey method with cross sectional design. Samples of this study were 120 students that were selected by using simple random sampling technique of 4th grade students at three elementary schools in the city of Bogor. The results showed that the social competence of children were at high level in every dimension (selfknowledge, self-management, knowing of the social environment, expert in building relationships). Factors that influence positively on the social competence of children were the active guidance of a mother when watching television, the number of hours that child use for reading, the number of hours that father use for reading, and age of father. Factors that negatively affect were the number of hours that father use for watching television, restrictions on reading a book by the mother, number of children's books, number of books father’s books, and age of mother. The study also found differences in treatment between mother of daughter and mother of the boy. Mother whose boy more actively guiding of the contents of television viewing than mother whose daughter.